Solid-state synthesis, characterizations and luminescent properties of EuBO3 phosphors with various Gd3+ concentrations for X-ray screen material application. (November 2022) - Angnanon, A.; Nualpralaksana, S.; Damdee, B.; Rajaramakrishna, R.; Chanlek, N.; Horprathum, M.; Kothan, S.; Kaewkhao, J.
Abstract: In the present work, EuBO3 phoshors doped with various Gd 3+ ion concentration, Eu1-X GdX BO3 ; (x = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 and 0.7), were synthesized by solid state reaction method at 900° for 18 h. Their crystal structure was determined by X-ray diffraction (XRD) technique showing triclinic EuBO3 (JCSD 01-089-7888) and hexagonal crystal EuBO3 (JCDD 00-013-0485). Structure dependence luminescence concentration quenching was observed. The photoluminescence behaviors of Eu 3+ in the phosphor material were investigated by the excitation and emission spectra which show the charge-transfer band (CTB) of O 2− →Eu 3+ . The excitation bands of Gd 3+ ions were observed at 275 nm ( 8 S7/2 → 6 I9/2 ) and 313 ( 8 S7/2 → 6 D7/2 ). The emission spectra displayed two prominent peaks of magnetic dipole ( 5 D0 → 7 F1 ) and electric dipole ( 5 D0 → 7 F2 ) transitions which signify the symmetry of the lattice. The CIE chromaticity coordinates were reddish-orange emission (x = 0.6635, y = 0.364) which corresponds to excited by the UVGL-25 Compact UV Lamp at 365 nm and X-ray Cu target (40 kV, 30 mA). Highlights: Eu(1-x) Gdx BO3 was successfully synthesized using solid state combustion technique. The structural dependent luminescence behaviour was observed in these phosphors. Luminescence spectra show highest emission intensity at 0.4 mol% of Gd2 O3 content. XPS technique indicated spin orbit coupling of Eu 3+ ions at 3d5/2 and 3d3/2 . SEM images for 0.4 mol% Gd2 O3 content show disrupted porous surface morphology.